Enhancing Nitrate Removal from Freshwater Pond by Regulating Carbon/Nitrogen Ratio - Chen, Rong; Deng, Min; He, Xugang; Hou, Jie (Frontiers in Microbiology, 2017)
Nitrogen accumulation is a serious environmental problem in freshwater ponds, which can lead to massive death of fish and shrimps as well as the eutrophication. The removal of nitrate by regulating the carbon to nitrogen (C/N) ratio and the underlying mechanisms were investigated. The nitrate removal system comprised 530-mL medium containing 5 mg/L NO3--N and 0–66.6 mg/L COD (i.e., C/N ratio of 0–13.3) and 20 g ponds sediments. When the C/N ratio was higher than 8, the nitrate removal efficiency nearly reached 100% during the incubation period and the accumulation of nitrite was negligible. When the C/N ratio was below 8, the nitrate removal efficiency was lower and significant nitrite accumulation occurred. The nitrate removal rate increased with the C/N ratio increased, which was ascribed to the increase in the absolute abundance of denitrifiers (nirS, nirK,and nosZ). Although both nirS-type and nirK-type denitrifiers were found in the sediments of freshwater pond, nirS-type denitrifiers were predominant. Dechloromonas was the major nirS-type denitrifier for nitrate removal in nirS-type with the C/N ratios above 5.33, while the majority of the nirK-type denitrifiers were unclassified. Thus, this study implied that the appropriate C/N ratio played an important role on the removal of excess nitrate from freshwater ponds.